EDUCAÇÃO EM/PARA DIREITOS HUMANOS COM A METODOLOGIA DA APRENDIZAGEM BASEADA EM PROBLEMAS : EDUCATION IN/FOR HUMAN RIGHTS WITH THE PROBLEM-BASED LEARNING METHODOLOGY - Yurie Moura da Silva, Danielle; Rosan Christino Gitahy, Raquel (Ponto de Vista Jurídico, 2024)
O objetivo geral da pesquisa foi analisar como a metodologia ativa da Aprendizagem Baseada em Problemas (PBL) pode auxiliar na construção do pensamento crítico reflexivo no que se refere aos Direitos Humanos. A metodologia utilizada foi a pesquisa qualitativa do tipo intervenção. Foram participantes 05 alunos do ensino médio de uma rede pública estadual e a professora que também atuou como pesquisadora. Para a aplicação da metodologia PBL, foi elaborado um problema com a temática injustiça/desigualdade social. Foram usados para a coleta de dados, a observação dos sete passos do PBL feitos no grupo durante a discussão do problema, os documentos de registro de todos os passos do PBL elaborados pelo relator dos grupos, e um documento de resolução do problema em formato de redação, que foi elaborado de forma colaborativa. A análise dos dados permitiu verificar que o PBL foi avaliado positivamente pelo grupo em função da sua estrutura e didática, de forma que, além de construírem conceitos sobre Direitos Humanos, possibilitou a aprendizagem mais ativa e colaborativa. PALAVRAS CHAVE: Educação; Direitos Humanos; metodologia ativa; aprendizagem baseada em problema. ABSTRACT The general objective of the research was to analyze how the active methodology of Problem-Based Learning (PBL) can help in the construction of reflective critical thinking with regard to Human Rights. The methodology used was qualitative research of the intervention type. Participants were 05 high school students from a public state network and the teacher who also acted as a researcher. For the application of the PBL methodology, a problem with the theme of social injustice/inequality was elaborated. For data collection, the observation of the seven steps of the PBL performed in the group during the discussion of the problem, the documents recording all the steps of the PBL prepared by the rapporteur of the groups, and a document of resolution of the problem in format of essay, which was prepared collaboratively. Data analysis allowed us to verify that the PBL was positively evaluated by the group due to its structure and didactics, so that, in addition to building concepts about Human Rights, it enabled more active and collaborative learning. Keywords: Education; Human rights; active methodology; problem-based learning. ABSTRACT The general objective of the research was to analyze how the active methodology of Problem-Based Learning (PBL) can help in the construction of reflective critical thinking with regard to Human Rights. The methodology used was qualitative research of the intervention type. Participants were 05 high school students from a public state network and the teacher who also acted as a researcher. For the application of the PBL methodology, a problem with the theme of social injustice/inequality was elaborated. For data collection, the observation of the seven steps of the PBL performed in the group during the discussion of the problem, the documents recording all the steps of the PBL prepared by the rapporteur of the groups, and a document of resolution of the problem in format of essay, which was prepared collaboratively. Data analysis allowed us to verify that the PBL was positively evaluated by the group due to its structure and didactics, so that, in addition to building concepts about Human Rights, it enabled more active and collaborative learning. Keywords: Education; Human rights; active methodology; problem-based learning.